Ekstraksi kombinasi ultrasonik dan enzimatis untuk senyawa asam klorogenat dari Cascara Kopi Arabika Kerinci - Lestari , Siti Marwah; Rahmaha, Vindi Annisa; Khairunnisa , Selda Vira; Salsabilla , Tiskha; Fadillah , Nur (Journal of Pharmaceutical and Sciences, 2026)
Arabica Coffee Cascara (CKA) has high potential as a source of bioactive compounds such as chlorogenic acid, which has antioxidant activity. The release of active compound can be optimized by combining ultrasonic and enzymatic methods, which are more efficient and environmentally friendly. The aim of this study was to examine the effectiveness of ultrasound-enzymatic-assisted extraction (UEAE) using water as a solvent for chlorogenic acid compound from CKA using Response Surface Methodology Box-Behnken Design (RSM_BBD). Three extraction parameters, such as sonication temperature (35-45°C), enzyme concentration (10-20 mg/g), and enzymolysis temperature (40-60°C), were designed to obtain optimal chlorogenic acid content. Based on the general trend data, results indicated that the highest chlorogenic acid content was 42.55 mg/g of dry extract, and was achieved under specific conditions: a sonication temperature of 40°C, an enzyme concentration of 10 mg/g, and an enzymolysis temperature of 60°C. Verification tests showed a value of 44.17 mg/g dry extract within the model’s prediction range with a 95% confidence level. The current quadratic RSM model with the existing factor design is not yet a reliable predictive tool and only serves to explore the range of operational extraction conditions.